Sharia Economic Dispute Resolution During Covid-19 Pandemic - Asriani, Asriani; surono, Surono; Kumar, Prodip (Universitas Islam Negeri Raden Intan Lampung, 2021)
The process of resolving a case, especially concerning business disputes, generally runs slowly, drags on, and takes a long time, at least three months. This condition will, of course, burden the litigants, especially in cases where the value of the material claim is small. To overcome this problem, the Supreme Court issued PERMA No. 2 of 2015 in conjunction with PERMA Number. 4 of 2019 which regulates the Settlement of Simple Claims (Small Claim Court). What is meant by Simple Claim Settlement. is a procedure for examining a civil lawsuit with a material claim value of a maximum of 500 million rupiahs. With this regulation, it is hoped that the dispute resolution procedure can be simpler, faster, and less expensive. This study examines the court process for simple lawsuits related to Sharia business cases during the Covid-19 pandemic. The aim is to find out how the court process works and how effective the mechanism is in serving the interests of justice seekers. This research is a qualitative descriptive study using a juridical normative approach. The results showed that during the pandemic, the implementation of the small claim court was carried out using the e-court facility, and has proven to be effective and efficient in serving justice seekers.